Use of a 3D stratigraphic model as tool for improved communication and risk assessment in large infrastructure projects. Issue 1 (April 2021) - Kahlström, M; Mortensen, P-A; Hauser, C; Hansen Børner, N
Abstract: As more work processes are moving into the digital space, such as collaborative BIM environments, the toolbox of the geotechnical engineer needs an update to efficiently keep track. Visualization of soil conditions in 3D space, using implicit modelling tools, is rapidly changing how geotechnical engineers engage with digital data. For a large railroad development in Norway, a 3D stratigraphic model is developed to act as a hub for soil interpretation, decision making and communication of geotechnical challenges and risks. Lithology is interpreted from all geotechnical boreholes and used as basis for the model together with a terrain model from GIS. The model is dynamically updated as new geotechnical soil investigations are performed and is actively used in the geotechnical design work. Overall, the 3D stratigraphic model is successfully applied for: (1) Visualization of geotechnical uncertainty with a classification based on radial distance to the borehole, (2) communication of sub-surface conditions and risk to project stakeholders and (3) efficiently exporting cross-sections as basis for geotechnical analysis.